Nonamagnesium diruthenium, Mg9Ru2 - Junhui Li; Huizi Liu; Yibo Liu; Bin Wen; Lifeng Zhang; Changzeng Fan (IUCrData)
A monoclinic phase with chemical composition of Mg9Ru2, nonamagnesium diruthenium, was obtained through high-pressure sintering of a mixture with an initial chemical composition of MgRuB. The Mg9Ru2 phase crystallizes in the C2/c space group with Z = 8 and is isotypic with the previously reported In0.74Ir3.3Mg17.96 and In1.9Ir3Mg17.1 phases.